The empowered investor : 7 principles for strategic wealth creation in a new financial world - Puempin, Cuno; Liechtenstein, Heinrich; Hashemi, Fariba; Hashemi, Brian; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book presents an innovative new framework consisting of seven key principles for strategic wealth creation. Illustrated through real world examples from interviews with highly successful private investors, the book provides a practical perspective grounded in sound academic research and practical experience.
Keywords: Science